The Leadership Behavior of the Heads of the Departments of Faculties of Physical Education and Sports Science and Its Relationship to Work Stress among Teachers - Sami Shahid, Basem; Mosa Jawad, Sondus (International Journal of Psychosocial Rehabilitation, 2020)
The research problem focuses on revealing the strength of the relationship and its direction between the leadership behavior of department heads and its relationship to work pressure among teachers in colleges of physical education and sports science that can give officials or decision-makers the ability to predict the level of work pressure. As for the aims of the research, to identify the leadership behavior of the department heads in the Faculties of Physical Education and Sports Science from the viewpoint of the teachers. Knowing the level of work stress among teachers. The two researchers used the descriptive method in the analytical method to suit the nature and nature of the research problem. The research sample included faculty members in some colleges of physical education and Iraqi sports, and the number was 150. A scale that includes two tools, the first to measure leadership behavior and the second to measure pressure, as the two researchers followed the following procedures: reviewing the literature and previous studies that dealt with the issue of leadership behavior and work pressure. The researchers have concluded the results of the study, which emphasized the measures of the relationship between the pattern of leadership behavior and the level of work stress and recommended that appropriate measures be taken in colleges of physical education and sports science to motivate department heads to rely on modern methods of leadership and management of departments, such as setting up training workshops for them in consulting offices.